Comparative evaluation of the Lithuanian public expenditure scale and structure - Bivainis, Juozas (Technological and Economic Development of Economy, 2005)
Since the restoration of independence (1990) significant changes were made in all aspects of Lithuania's economy. The achievements of the country in the area of economic development are obvious – the essential preconditions for faster economic growth and approaching to the social‐economical life standards of advanced countries were created during a transition period. The exceptional role between different factors of social‐economical development of the country is ascribed to public finance. The statistics shows persuasive common world tendency of public expenditure growth. It can be explained in relation to historical changes of the sense, role and principles of management. The comparison of 1995–2001 year indicators, describing the public expenditure of Lithuania with the other countries including four new residents of the EU (Czech Republic, Estonia, Latvia, Poland), five old ones (Austria, Belgium, Denmark, Germany, United Kingdom) and two representatives of CIS (Belorus and Rusia) is resulted by certain main conclusions. The Republic of Lithuania occupies one from below place in a diminution row between twelve countries which were selected for the investigation. It is a characteristic feature of the last investigated year (2001) as well as an average of three investigated years (1995, 1998, 2001). The structure of public expenditure on function section of our country is similar to one of other new members of the EU, Lithuania made steps during 1995–2001 towards the structure of public expenditure on function and economic classifications the countries – old residents. The relative changes of Lithuanian public expenditure in function section were the largest between all the investigated countries, while the change of total public expenditure (% of GDP) was the smallest. The disclosed comparative estimates of public expenditure on these scale and structure and its tendencies can be used as a reference point for creating the fiscal policy, improving public sector management and implementation of national budget reforms. These estimates may also serve as arguments for tax reforms what is a topical issue for the present time.Article in Lithuanian.Lietuvos valstybės išlaidų masto ir struktūros lyginamieji vertinimaiSantrauka. Atlikta Lietuvos 1995–2001 metų valstybės išlaidų lyginamoji analizė, vertinant penkias naująsias ES nares, penkias ES senbuves, taip pat Lietuvos kaimynes Baltarusiją ir Rusiją (NVS šalys), leido nustatyti tam tikrus dėsningumus. Iš dvylikos tirtų valstybių Lietuva pagal valstybės išlaidų rodiklį (proc. BVP) yra mažėjančios eilės pabaigoje ir eina prieš Rusiją. Pagal išlaidų struktūrą funkcijų pjūvyje Lietuva neišsiskiria iš bendro naujųjų ES narių fono ir per 1995–2001 metus sumažino struktūrinius skirtumus nuo ES senbuvių. Iš visų nagrinėtų šalių Lietuvos valstybės išlaidų santykiniai pokyčiai pagal atskiras išlaidų grupes funkcijų pjūvyje yra didžiausi, o visų valstybės išlaidų (proc. BVP) pokytis yra mažiausias. Valstybėms nebūdinga perskirstyti daugiau kaip pusės sukurto bendrojo vidaus produkto ‐ priartėjus prie tokios ribos pastebima išlaidų mažėjimo tendencija. Pateikti valstybės išlaidų masto ir struktūros bei jų dinamikos lyginamieji vertinimai gali būti orientyru planuojant šalies fiskalinės darnos rodiklius, tobulinant viešojo sektoriaus valdymą, įgyvendinant nacionalinio biudžeto reformas.Reikšminiai žodžiai: valstybės išlaidos, išlaidų struktūra, pokyčiai, lyginamoji analizė.First Published Online: 21 Oct 2010